Herpes zoster: A Review of Clinical Manifestations and Management - Patil, Anant; Goldust, Mohamad; Wollina, Uwe (Viruses, 2022)
The Varicella-zoster virus (VZV) or human herpes virus 3 is a neurotropic human alpha herpes virus responsible for chickenpox/varicella and shingles/Herpes zoster (HZ). This review will focus on HZ. Since HZ is secondary to varicella, its incidence increases with age. In children and youngsters, HZ is rare and associated to metabolic and neoplastic disorders. In adults, advanced age, distress, other infections (such as AIDS or COVID-19), and immunosuppression are the most common risk factors. HZ reactivation has recently been observed after COVID-19 vaccination. The disease shows different clinical stages of variable clinical manifestations. Some of the manifestations bear a higher risk of complications. Among the possible complications, postherpetic neuralgia, a chronic pain disease, is one of the most frequent. HZ vasculitis is associated with morbidity and mortality. Renal and gastrointestinal complications have been reported. The cornerstone of treatment is early intervention with acyclovir or brivudine. Second-line treatments are available. Pain management is essential. For (secondary) prophylaxis, currently two HZV vaccines are available for healthy older adults, a live attenuated VZV vaccine and a recombinant adjuvanted VZV glycoprotein E subunit vaccine. The latter allows vaccination also in severely immunosuppressed patients. This review focuses on manifestations of HZ and its management. Although several articles have been published on HZ, the literature continues to evolve, especially in regard to patients with comorbidities and immunocompromised patients. VZV reactivation has also emerged as an important point of discussion during the COVID-19 pandemic, especially after vaccination. The objective of this review is to discuss current updates related to clinical presentations, complications, and management of HZ.